Profitabilitas dan Efisiensi Usaha Ternak Ayam Broiler di Tasikmalaya Jawa Barat - Agus Santosa; Unang Atmaja (Jurnal Dinamika Sosial Ekonomi, 2002)
The key of the Indonesian government as far as the livestock sector is concerned is the expansion of the poultry industry, in particular the broiler industry. Policy maskers see the broiler industry as an important source of animal protein since in comparison with cattle poultry are efficient converters of feed grains into meat.  The research area is Tasikmalaya, as is considered to be a potential broiler production area that develops better among regions in the West Java. This study is focused on broiler business pattern, both partnership and autonomous, using the profitability and efficiency to measure the tingkat of comparative advantage. Policy Analysis Matrix (PAM) based on primary data were constructed for the different pattern of production system. Scale of production was also taken into account. The larger were farmers who exerted more than 2000 heads per production cycle. The study find that broiler production in Tasikmalaya is an efficient industry and can exist without any protection. The partnership and the larger farmers enjoy more profit relative to the autonomous and the smaller ones. Tingkats of efficiency and profitability are influenced by production factor prices of feed and DOC as well as broiler. Other finding is that government plant to set 80% imported tariff on chicken leg quarter (broiler part) can not avoid yet to makes the domestic product of broiler less competitive in the domestic market. Key Words: efficiency, profitability, competitive advantage.